Industry 4.0 related innovation and firm growth - Vanessa Behrens; Markus Trunschke (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
In this paper we explore the relationship between innovative firms that patent technology related to Industry 4.0 and their economic performance. By applying the new patent cartography developed by the EPO that identifies firm's 4.0 patents, this is one of the first large-scale, systematic studies on the impact of 4.0 technologies. Since 4.0 patents are more likely to be general purpose technologies, firms with 4.0 patents should be in a better position to increase their sales as 4.0 technology has on average a wider industrial applicability. Results of our Fixed Effects Least Squares regressions and Dynamic Panel Model suggest that 4.0 patent stock is positively associated to sales and that this effect is significantly larger than the effect of Non-4.0 patent stock. These effects are found to be decreasing with firm size.
Keywords: L25; O14; O33; 330; Industry 4.0; Patents; Firm Performance; Sales Growth